2019
DOI: 10.1002/2211-5463.12697
|View full text |Cite
|
Sign up to set email alerts
|

Degradation kinetics of α‐conotoxin TxID

Abstract: α‐Conotoxin (CTx) TxID is a potent α3β4 nicotinic acetylcholine receptor (nAChR) antagonist that has been suggested as a potential drug candidate to treat addiction and small cell lung cancer. The function and structure of TxID have been well‐studied, but analyses of its stability have not previously been reported. The purpose of this study was to analyze the stability and forced degradation of TxID under various conditions: acid, alkali, water hydrolysis, oxidation, light, thiols, temperature, ionic strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…They can specifically inhibit muscle-type nicotinic acetylcholine receptors, causing organ numbness, vomiting, dizziness, respiratory failure, and death. [29][30][31]…”
Section: α-Conotoxinmentioning
confidence: 99%
See 1 more Smart Citation
“…They can specifically inhibit muscle-type nicotinic acetylcholine receptors, causing organ numbness, vomiting, dizziness, respiratory failure, and death. [29][30][31]…”
Section: α-Conotoxinmentioning
confidence: 99%
“…Notably, GI and MI are the most toxic of the α‐conotoxin acting on the muscle‐type acetylcholine receptors. They can specifically inhibit muscle‐type nicotinic acetylcholine receptors, causing organ numbness, vomiting, dizziness, respiratory failure, and death 29‐31 …”
Section: Types Of Conotoxin That Can Be Used To Prevent Wound Scar Hy...mentioning
confidence: 99%
“…To further improve the selectivity of TxID, the researchers used a series of non-natural amino acids to substitute Serine at position 9 of TxID and found that [S9K]TxID displayed a specific and potent inhibitory effect towards α3β4 nAChRs with an IC 50 of 6.9 nM [ 16 ]. The stabilities of TxID under multiple conditions were evaluated by UPLC based on recommendation of International Conference on Harmonization [ 17 ]. The purpose of the present study was to evaluate the effect of α3β4 nAChRs antagonists TxID and [S9K]TxID in nicotine-induced behaviors, by investigating whether TxID and [S9K]TxID would alter the acquisition and relapse of nicotine-induced CPP, and physical acute nicotine behaviors in mice.…”
Section: Introductionmentioning
confidence: 99%